Penerapan Pembangkit Listrik Tenaga Angin Untuk Penerangan Lampu Jalan Dipesisir Pantai Teluk Uber Secara Otomatis Berbasis IoT - Azharry, Deni; Maulina, Firly; Sulistyo, Eko; Ocsirendi, Ocsirendi (Jurnal Inovasi Teknologi Terapan, 2025)
Renewable energy, particularly wind power, offers a relevant solution to address climate change challenges and the growing electricity demand, especially in coastal areas such as Pantai Teluk Uber, Bangka Belitung. This study develops a Wind Power Generation System (PLTB) based on the Internet of Things (IoT) for real-time monitoring via smartphones. The system utilizes a wind turbine equipped with an anemometer sensor for wind speed, an INA219 sensor for monitoring current and voltage, and a BH1750 sensor for measuring light intensity. The collected data is transmitted to an IoT platform for remote monitoring. Additionally, the system was tested for battery charging and discharging, with charging requiring approximately 8 hours at an average current of 1 A, and discharging lasting around 10 hours with a 12V 10W DC lamp load. The maximum power generated by the system is 6.73 watts at a wind speed of 9 m/s, while the minimum power recorded is 0.35 watts at a wind speed of 2 m/s. The results show that the IoT-based PLTB system can efficiently provide energy for nighttime lighting and other applications.